Virtual-real comparison technique used on sport simulation and analysis - Qiu, X. J.; Wang, Z. Q.; Xia, S. H.; Wu, Y. D. (IEEE International Conference on Signal Processing, 2004)
The simulation and analysis of human motion is a popular issue in simulation area. It is highly valued in sport motion training and analysis. A method based on computer vision technologies is presented to achieve the function that the simulated motion in sport simulation system and the motion in sport video are presented on the same screen and at the same view point. So we can quickly and accurately find the difference between the athlete motion in sport video and the simulated motion. It is very helpful to the training of athletes.